Isolation and Identification of Bacterial Burn Wound Infection in Iraqi Patient - Jenan A. Ghafil; May. T. flieh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Burns are one of the most common and devastating forms of trauma. Patients with serious thermal injuryrequire immediate specialized care in order to minimize morbidity and mortality.In current study, 120samples were collected from 120 patients suffering from contaminated burns. The study was conducted afterobtaining ethical approvals from the ethics committee in the Department of Biology, College of Science,University of Baghdad as well after obtaining the patients ’consent. Samples are collected from patientsafter they have stopped using antibiotics for 48 hours.After the swabs had been cultured on different media,conventional biochemical tests to identify bacterial isolates and antimicrobial sensitivity to the most commonantibiotics were performed by vitek 2 compact .The results showed that the highest percentage of bacterialspecies was Proteus mirabilis (31.1 %). The percentage of isolation of P. aeruginosa was 17.78%. The lowestpercentage of bacterial isolates that isolated from infected wound was found in case of Staphylococcusaureus, Pseudomonas fluorescens, Acinetobacterhaemolyticus, Burkholderiacepacia, Salmonella ser.gallinarum, Sphingomonaspaucimobilis, Comamonas testosterone with 2.2 % for each isolate.